An empirical analysis: Risk attitudes of Managers, Doctors and Accountants in Cyprus - Tsokkou, Xenia (2016)
This research analyses the differences in risk attitudes of managers, doctors and accountants. By adopting an empirical approach, a sample of 161 Cypriots professionals and university students of management, medicine and accounting aged between 17 and 46+ was collected and examined. In order to identify and analyze risk attitudes, participants were given questionnaires which consisted of general questions regarding risk, hypothetical scenarios and real life situations. The results indicate that risk preferences vary across occupations and more specifically managers tend to be risk lovers, doctors tend to be risk averse whereas the accountants tend to be risk neutral toward risk lovers. Also, the study concludes that gender and age do not constitute a crucial determinant on risk preferences. Therefore, the risk attitudes of individuals within the same involvement field do not vary with gender and age. The final indication is that professional doctors display risk aversion in all amounts of money as they prefer to insure their income regardless its level, whereas managers and accountants display risk aversion only for higher levels of income.